THE EFFECTIVENESS OF BLENDED LEARNING ON LEARNING MOTIVATION AND STUDENT LEARNING OUTCOMES - Ambiyar Ambiyar; Misrol Ayani; Deviana Ridhani; Pirdo Adi Putra (Jurnal Scientia, 2023)
The effectiveness of blended learning at SMK Negeri 1 Kinali on student learning outcomes and motivation. This study was able to determine the following: a) Knowing the variations in learning motivation and learning outcomes between students taught in blended learning and students taught in traditional classes; b) knowing the increase in learning motivation and student learning outcomes due to the use of mixed learning. It is a quasi-experiment to do this kind of study. 64 randomly selected students form the study population. Data collection techniques include written exams and surveys. Parametric statistics were utilized to examine and test the data (F-test and t-test). These are the research's results. a) Between students who study mixed learning and students who study conventional learning, there are differences in learning outcomes with sig. 0.000 with an average of 13.38 and a difference in learning motivation with sig. 0.012 with an average of 4.75. b) Employing blended learning improves student learning outcomes with a sig. 0.000 average increase of 38.22 and enhances student learning motivation by an average of 13.56.